Geração de personagens virtuais simulando o processo reprodutivo de seres diplóides - Vieira, Roberto César Cavalcante (2007)
In many Computer Graphics aplications, virtual character are needed, and can be used in animations, educational softwares, as an avatar, chosen to represent an user in a virtual reality application, etc. Usually, the available models is very limited. Therefore, combinations of hair color, cloth texture, and skin color are used to increase the selection space. In this paper, human reproduction is mimicked to produce an unlimited number of characters, which inherit traits from two parents. The meshes of all models are constructed based on control parameters that are distributed as genes among a group of chromosomes. Hence, the implementation consists of a pre-selected distribution of characteristics, represented as control parameters, over a pre-determined number of chromosome pairs for both parents; followed by a simulation of the father’s and mother’s gametes generation; which are randomly combined in a simulated fecundation. The diversity is ensured in three random processes: 1) random exchange of segments during crossover; 2) random alignment of homologous chromosomes at metaphase I of meiosis; and 3) random union of male and female gametes during fecundation.